2013
DOI: 10.1016/j.bmc.2013.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, computational modeling and cytotoxicity of a series of meso-phenyl and meso-thienyl-BODIPYs

Abstract: A series of twenty-two BODIPY compounds were synthesized, containing various meso-phenyl and meso-thienyl groups, and their spectroscopic and structural properties were investigated using both experimental and computational methods. Further functionalization of the BODIPY framework via iodination at the 2,6-pyrrolic positions was explored in order to determine the effect of these heavy atoms on the photophysical and cytotoxicity of the meso-aryl-BODIPYs. BODIPYs bearing meso-thienyl substituents showed the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 57 publications
7
66
0
Order By: Relevance
“…However, the quantum yields for the meso -alkenyl, alkynyl, pyrrolyl, and thienyl-BODIPYs 20 – 25 were appreciably lower, particularly for 20 , the fluorescence of which was essentially quenched, due to the greater freedom of rotation for these smaller groups increasing the energy lost to non-radiative decay. [43] Boron substitution had no significant effect on the absorption and emission wavelengths, but did influence the fluorescence quantum yield. Although boron substitution with two methoxy groups significantly increased the quantum yield of BODIPY 15 ( Φ f =1.0) relative to 13 ( Φ f = 0.57), substitution with two ethyl groups reduced the quantum yield of BODIPY 12 ( Φ f =0.32) relative to 11 ( Φ f =0.83).…”
Section: Resultsmentioning
confidence: 97%
“…However, the quantum yields for the meso -alkenyl, alkynyl, pyrrolyl, and thienyl-BODIPYs 20 – 25 were appreciably lower, particularly for 20 , the fluorescence of which was essentially quenched, due to the greater freedom of rotation for these smaller groups increasing the energy lost to non-radiative decay. [43] Boron substitution had no significant effect on the absorption and emission wavelengths, but did influence the fluorescence quantum yield. Although boron substitution with two methoxy groups significantly increased the quantum yield of BODIPY 15 ( Φ f =1.0) relative to 13 ( Φ f = 0.57), substitution with two ethyl groups reduced the quantum yield of BODIPY 12 ( Φ f =0.32) relative to 11 ( Φ f =0.83).…”
Section: Resultsmentioning
confidence: 97%
“…The product was purified by silica gel flash column chromatography using mixtures of petroleum ether and dichloromethane for elution. 34,43 General Procedure for O-BODIPYs using Method A. In an oven-dried flask, BODIPY (20.0 mg, 0.062 mmol) and NaOMe (21.0 mg, 0.389 mmol) were dissolved in anhydrous methanol (2 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Studies have shown that incorporation of iodines at the 2,6-positions of BODIPYs leads to enhanced intersystem crossing, whereas addition at the 3,5-positions promotes fluorescence [30]. In addition, phototoxicity depends on the substituents on the 2,6-diiodo-BODIPYs, and is favored by electron-donating 8-aryl groups [2326]. …”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported the synthesis and cytotoxicity properties of near-IR mono-and di-indolylstyryl-BODIPYs [38], and a series of 2,6-diiodo-BODIPYs [26]. Among these, the mono- indolylstyryl-BODIPYs showed high uptake by HEp2 cells with no detectable cytotoxicity in the absence or presense of light, while the 8-(3,5-dimethyoxyphenyl)-2,6-diiodo-1,3,5,7-tetramethyl-BODIPY ( 1 ) showed high phototoxicity (IC 50 = 4 µM at 1.5 J/cm 2 ) but remained non-toxic in the dark (IC 50 > 400 µM).…”
Section: Introductionmentioning
confidence: 99%